2022
DOI: 10.1007/s42770-022-00743-z
|View full text |Cite
|
Sign up to set email alerts
|

Spike protein of SARS-CoV-2 variants: a brief review and practical implications

Abstract: The scientific community has been alarmed by the possible immunological evasion, higher infectivity, and severity of disease caused by the newest variants of SARS-CoV-2. The spike protein has an important role in the cellular invasion of viruses and is the target of several vaccines and therapeutic resources, such as monoclonal antibodies. In addition, some of the most relevant mutations in the different variants are on the spike (S) protein gene sequence that leads to structural alterations in the predicted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 240 publications
0
27
0
Order By: Relevance
“…The H69/V70 deletion is not present in the SARS-CoV-2 variants Delta and Omicron BA.2; therefore the L452R RT-qPCR was included into the RT-qPCR large-scale screening platform [ 13 , 16 ]. Running two RT-qPCRs, each directed against one specific key mutation, e .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The H69/V70 deletion is not present in the SARS-CoV-2 variants Delta and Omicron BA.2; therefore the L452R RT-qPCR was included into the RT-qPCR large-scale screening platform [ 13 , 16 ]. Running two RT-qPCRs, each directed against one specific key mutation, e .…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the analytical performance characteristics of the existing ΔH69/V70 RT-qPCR included in our Variant-PCR [13] for Moreover, the fluorescence intensity was moderately reduced for the degenerate probe compared to the original probe targeting the ΔH69/V70 present in the SARS-CoV-2 Alpha variant (TWIST control) (S1A Fig) . However, the sensitivity of the ΔH69/V70 RT-qPCR was unchanged including the degenerate ΔH69/V70 probe instead of the original probe, as shown by a dilution row of the TWIST standard (Alpha variant) (Table 2; S1B Fig) . The sensitivity of the original primer and probe of the ΔH69/V70 RT-qPCR was determined in a previous study [13]. The H69/V70 deletion is not present in the SARS-CoV-2 variants Delta and Omicron BA.2; therefore the RT-qPCR was included into the RT-qPCR large-scale screening platform [13,16]. Running two RT-qPCRs, each directed against one specific key mutation, e.g.…”
Section: A Degenerate δH69/v70 Probe Is Specific For Omicron Detectionmentioning
confidence: 99%
“…The H69/V70 deletion is not present in the SARS-CoV-2 variants Delta and Omicron BA.2; therefore the L452R RT-qPCR was included into the RT-qPCR large-scale screening platform (12,14). Running two RT-qPCRs, each directed against one specific key mutation, e .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Variants of Concern (VOC) are considered a collection of variants carrying mutations in the genome that increase transmission ability, inhibit the neutralization of antibodies, and escape from the immune system. Interestingly, the Spike (S) gene of SARS-CoV-2 encodes a spike protein that plays a role in the entry of the virus into the host through interaction with the hACE2 receptor (Ovsyannikova, Haralambieva et al, 2020) and is the excellent target of vaccines and monoclonal antibodies (Candido, Eich et al, 2022). However, the previous research indicated that the S gene has a much faster rate of nucleotide substitution (Berrio, Gartner et al, 2020) and the RBD region of this gene has a more rapid mutation rate of 2 to 3 fold, respectively, compared to the mean of the genome (Chaw, Tai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%